Strategy for Building Sharia-Conscious Competitiveness in Small and Medium Enterprises Based on Local Wisdom - Karyono, Otong; Kamiruddin, Kamiruddin (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2024)
This research aims to answer how to build a competitive strategy to increase competitive advantage based on a sharia economic perspective which is the basis for developing the strategy model. This research method is qualitative research with the main data source obtained from observations and interviews with informants selected in this research. Sampling was carried out using purposive sampling with the informant subjects being songko recca business owners and the local government in charge of it. This research produced several important findings including strategy, constraints, and competitive advantage models referring to Michael Porter's competitive strategy theory. The strategies that are considered important to implement are strategies oriented toward price, quality, and human resources. The obstacle faced is that there is still a gap between customer expectations and reality so the ideal competitive advantage strategy model for small and medium businesses based on local wisdom is still based on customs that have been passed down from generation to generation accompanied by forms, philosophical values, and unique characteristics. Contained in the craft and maintains the motif smoothly and naturally